Centro de educación técnico Agrícola Usme (2021)
The Usme Agricultural Technical Education Center is located in the city of Bogotá, specifically on the southern periphery of the town of Usme, on the border between the urban and rural areas of the city. This project seeks to meet the educational needs of the sector through the architectural design of an educational facility with a capacity for 3,328 people, located on a 30,090m2 lot; Likewise, it has an area of 9,537m2 for cultivation and educational areas that promote academic and research activities.